The effects of blood flow restriction on measures of gross motor coordination during the wingate anaerobic test - Hoover, D. L.; Whicker, J.; Cross, J. E.; Giammalva, O. J.; Henderson, D. D.; Hoover, S. J.; Lyons, T. S.; Zolp, A.; Vidic, Z. (ISBS Proceedings Archive (Michigan), 2023)
To date little research has addressed the impact of blood flow restriction (BFR) training upon gross motor coordination measures (GMCM) during a wide variety of maximal activities. The purpose of this study was to assess the effects of BFR on GMCM exhibited during maximal cycling. The performance of 14 females between the ages of eighteen and thirty-five were analyzed during the Wingate Anaerobic Test (WAnT). The participants completed the test under two conditions, using BFR and without. Results showed statistically significant differences (p <= 0.05) between conditions for dependent variables assessed throughout this common 30 second test of maximal cycling. These findings suggest that BFR negatively influenced GMCM exhibited during the WAnT.